RETAINING HEALTH ACTIVITIES ELEMENTARY SCHOOL TEACHER IN WORKING CONDITIONS IN THE MOUNTAINOUS REGION - Oleksandra Khallo (Vasyl Stefanyk Precarpathian National University, 2015)
This article describes how to create retaining health educational environment as a factor of performance intended life goals and objectives, its purpose and self-improvement. The notion educative and retaining health environment is analyzed. Active position illustrated subjective, based on an understanding of their health in a residence in the mountain environment